Cultural Geography of Kathak Dance: Streams of Tradition and Global Flows. In Cosmopolitanism and Regionalism in Indian Cultural Dynamics VOL. XVIII Edited by Cristina Bignami and Ewa Dębicka-Borek (JAGIELLONIAN UNIVERSITY INSTITUTE OF ORIENTAL STUDIES, 2016)
The article deals with the modern history of Kathak, explored from regional perspectives. It focuses on the Lucknow gharānā (“school”) of Kathak, which sprung up mainly in courts and salons of colonial Avadh as a product of Indo-Islamic culture. The paper investigates how the shift of hereditary artists from Lucknow to Delhi affected their tradition in newly founded, state-supported institutions. It also examines various trends of further modernization of Kathak in globalized, metropolitan spaces. The tendency of Sanskritization in national dance institutes (Kathak Kendra) is juxtaposed with the preservation of ‘traditional’ form in dance schools of Lucknow (nowadays becoming more provincial locations of Kathak tradition) and innovative / experimental tendencies. The impact of regional culture, economic conditions and cosmopolitanism are regarded as important factors reshaping Kathak art, practice and systems of knowledge transmission. The paper is based on ethnographic fieldwork, combined with historical research, conducted in the period 2014–2015